2018
DOI: 10.1002/jmri.26181
|View full text |Cite
|
Sign up to set email alerts
|

Phase contrast MRI measurements of net cerebrospinal fluid flow through the cerebral aqueduct are confounded by respiration

Abstract: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…Also, future studies should include multiple PC sequences with different velocity encodings which would allow simultaneous examination of the changes within CSF fluid dynamics together with hemodynamic measures of the arterial and venous counterparts. Changes in AoS velocity, pressure gradients, and flow measures due to heart cycle changes, respiration or exercise should be monitored in future studies [36]. As such, a recent study demonstrated that respiratory-induced pressure gradients-the force driving the net CSF flow through the AoS-dominate over the cardiac component which is responsible for more frequent and pulsatile peak flow rates [37].…”
Section: Discussionmentioning
confidence: 99%
“…Also, future studies should include multiple PC sequences with different velocity encodings which would allow simultaneous examination of the changes within CSF fluid dynamics together with hemodynamic measures of the arterial and venous counterparts. Changes in AoS velocity, pressure gradients, and flow measures due to heart cycle changes, respiration or exercise should be monitored in future studies [36]. As such, a recent study demonstrated that respiratory-induced pressure gradients-the force driving the net CSF flow through the AoS-dominate over the cardiac component which is responsible for more frequent and pulsatile peak flow rates [37].…”
Section: Discussionmentioning
confidence: 99%
“…Yildiz et al found that respiratory effects are averaged out at conventional, cardiac-gated PC-MRI compared to real-time PC-MRI ( Yildiz et al, 2017 ). Furthermore, in a recent study, Spijkerman et al used respiratory gated PC-MRI and found that net CSF flow quantity at the aqueductal level was affected by breathing in healthy subjects, but did not affect conclusion about net flow direction ( Spijkerman et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It represents a recent acquisition intended to modify the theories on the pathogenesis of hydrocephalus (dilation of the ventricular system) the fact that the cerebrospinal fluid is reabsorbed partly through the lymphatic system of the nasal mucosa (in fact the cerebral parenchyma does not contain lymphatic vessels) to which it reaches following the subarachnoid spaces that line the olfactory bulbs. The cerebro-spinal liquid flow analysis with Phase Contrast Magnetic Resonance Imaging (PCMRI) [149] [150], shows that the CSF circulation at the level of the ventricular system and of the subarachnoid spaces is a dynamic oscillatory process synchronized with cardiac contractions. To better define this process we can imagine that the brain "pulsates" continuously, driven by cardiac contractions.…”
Section: The Proton Motive Force and Protons Role In Biological Liquimentioning
confidence: 99%